Coir Fibres: A best use of waste material - Saifee, Sakina Najmuddin (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This paper is an attempt to make the best use of the waste material obtained from the coconut trees. The coconut husk which is assumed to be of no use; actually is very much useful in day to day life because of its physical, chemical and mechanical properties. The coconut husk is widely adopted as an engineering material also due to its high tensile strength and elasticity. The results obtained from various tests have also been shown which gives us a clear idea about variation of different properties depending upon different fibre composition. The components, advantages, disadvantages as well as application of fibers of the coconut husk are discussed in this paper so that it spreads awareness of using coconut fiber as construction material in civil engineering